The effect of smoking on serum and saliva AMP-aminohydrolase (AMPDA) and adenosine aminohydrolase (ADA) activities - Abdulbari, Alaa Shawqi; Atiroğlu, Vesen (Iraqi Journal of Science, 2025)
Adenosine deaminase (ADA), also referred to as adenosine aminohydrolase, is a key enzyme that plays a crucial role in purine metabolism. AMP-aminohydrolase, also known as AMP deaminase (AMPDA), facilitates the conversion of adenosine monophosphate (AMP) into inosine monophosphate (IMP). Cigarettes primarily consist of various substances. This study aimed to investigate the influence of cigarettes smoking on serum and saliva ADA and AMPDA activities, exploring the diagnostic potential of these enzymes in smoking- related diseases. Two hundred twenty subjects were enrolled, including 100 healthy smokers and 120 healthy non-smokers with measurement being made of serum and saliva ADA and AMPDA activities as well as complete blood count (CBC). There were highly significant increase in saliva ADA and AMPDA activities in smokers’ group in comparison to non-smokers as well as significant increase in serum ADA and AMPDA activities of smokers’ group in comparison to non-smokers group. The current study indicates that serum and saliva ADA and AMPDA levels increase in smokers due to effect of cigarettes smoking. The findings strongly suggest the potential of saliva AMPDA as a diagnostic marker for tongue cancer, as well as the role of ADA in diagnosing lung disease and coronary artery disease associated with prolonged smoking.